Family Ownership, Commisioners Independence and Corporate Social Responsibility in Indonesian Corporate - Siti Nuke Nurfatimah (Universitas Kuningan, 2018)
This study examined the effect of family ownership percentage rate on the disclosure of CSR information by family companies in Indonesia after the establishment of regulations issued by the Ministry of Environment in 2012. Disclosure of CSR is measured by content analysis method which refers to the GRI G3.1. In addition, this study also added a moderating effect, namely independent commissioners who acting as independent supervisors of a company. Independent commissioners are measured using the percentage of independent commissioners in the company. This study used a samples of all family companies in Indonesia except financial companies for 2013 to 2015. The hypothesis testing was carried out using panel data regression analysis both before and after involving moderating effects.